What Predicts Mortality in Essential Tremor? A Prospective, Longitudinal Study of Elders - Zubair, Adeel; Cersonsky, Tess E. K.; Kellner, Sarah; Huey, Edward D.; Cosentino, Stephanie; Louis, Elan D. (Frontiers in Neurology, 2018)
Objective: Essential tremor (ET) is among the most common neurologic diseases. Although in the past it was considered a benign condition, recent research has demonstrated increased risk of mortality. To date, however, no studies have examined predictors of mortality in ET. Methods: In a longitudinal, prospective study of 141 elders with ET, we used Cox proportional-hazards models to estimate hazard ratios (HRs) for death. Results: The mean baseline age was 81.1 ± 8.8 years. During the follow-up interval, 27 (19.1%) died. Average time from baseline to death was 12.3 ± 8.7 months (range = 0.3 – 31.2). In univariate Cox regression models, older age (HR = 1.16, p <0.001), lower Montreal Cognitive Assessment score (HR = 0.88, p = 0.004), higher Clinical Dementia Rating (CDR) score (HR = 4.53, p<0.001), higher score on the Geriatric Depression scale (GDS) (HR = 1.07, p = 0.048), less balance confidence (HR = 0.98, p = 0.006), more falls (HR = 1.11, p = 0.003), and more tandem mis-steps (HR = 1.53, p = 0.004) were associated with increased risk of mortality. In the final multivariate Cox model, older age (HR = 1.14, p = 0.005), higher CDR score (HR = 3.80, p = 0.002) and higher GDS (HR = 1.11, p = 0.01) were independently associated with increased risk of mortality. Conclusions: This study highlights several independent predictors of mortality in elderly ET; clinicians should consider screening for depressive symptoms, assessing cognition and tracking CDR scores, and assessing balance while evaluating patients with ET.